slove for x and y

Asked by geethika | 9th Feb, 2010, 05:19: AM

Expert Answer:

(a-b)x + (a+b)y = a2 - 2ab - b2 .......(1)

(a+b)(x-y) = a2 + b2   ............(2)

Adding (1) and (2),

(a-b)x + (a+b)x = a2 - 2ab - b2 + a2 + b2 

2ax = 2a2 - 2ab

x = (a - b)

Use this result in (2) to find y,

(a+b)(x-y) = a2 + b2 

(x-y) = (a2 + b2)/(a+b)

y = (a - b) - (a2 + b2)/(a+b)

= [(a - b)(a+b) - (a2 + b2)]/(a+b)

= -2b2/(a+b)

Regards,

Team,

TopperLearning.

 

Answered by  | 9th Feb, 2010, 10:25: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.